ECOLOGICAL STUDIES ON THE COMMUNITY OF MOSSES AT LANGHOVDE REGION, ANTARCTICA - Tatsuro MATSUDA (National Institute of Polar Research, 1964)
The ecological observation was made on the vegetative growth of shoots of Ceratodon purpureus and Bryum inconnexum. The number of green leaves and the production of rhizoids of the mosses were investigated. The community of the mosses stunted by blue green algae was observed (Figs. 9-a, -b, -c) and the growth lines in the cushion formed by Ceratodon purpureus were shown (Fig. 8). In Bryum inconnexum, the rhizoid and 14-17 leaves appear alternately on the stem (Fig. 13), and thus the rhizoidal parts of the stem of each individual are seen as the rhizoidal belts in the cross section of the cushion formed by Bryum inconnexum (Fig. 14). Therefore, it may be considered that the rhizoidal belts show the periodicity of the growth of Bryum inconnexum community. In the present paper, two types of the growth form of the cushion of Antarctic mosses have been discussed.